The development and psychometric properties of the persian linguistic inquiry and word count (P-LIWC): Emotions and cognitive processes categories - Mohammad Ali Soltani; Peyman MamSharifi; Reza Salehi Chegeni; Ali Safari; Soudabeh Ershadi Manesh; Hamidreza Keshavarz; Majid Afshari; MohamadSajad Ghafouri; Mojtaba Mohammadi; Fateme Tavakoli (مجله علوم روانشناختی)
Background: Linguistic Inquiry and Word Count (LIWC) are known as indicators of vocabulary in texts. Specifically, with the help of algorithms and computational processes, it can analyze elements such as emotions, cognitions, attitudes, vocabulary, language style and social communication in texts, and the lack of a Persian version was one of the most important reasons for conducting this research. Aims: The purpose of this research was to develop and examine the psychometric features of the Persian Linguistic Inquiry and Word Count in categories of Affect and Cognitive Processes. Methods: The present research method was descriptive and correlational. The method of developing categories of cognitive processes and affect consists of several stages. The development of the dictionary started with the initial translation of the words of the LIWC-22, and then, a huge corpus of Persian texts was analyzed to maximize the coverage of words of each category in the Persian language using text analysis methods. In the next step, the words were evaluated by psychologist judges, and then linguists determined the lemma of the approved words in order to distinguish different forms of the word. After completing these steps, in order to check the reliability of the dictionaries of cognitive processes and affect and their subcategories, Cronbach's alpha and Kuder-Richardson 20 were calculated, and then to check the external validity, the equivalence of the Persian Linguistic Inquiry and Word Count (P-LIWC) with the original English version of LIWC-22 was analyzed. Results: The results showed that all categories of emotions and cognitive processes in the P-LIWC had a significant correlation with the final English version of LIWC-22 (p<0.01) and this tool has good validity and reliability. Conclusion: It can be concluded that this software is used in a wide range of research fields and analysis of Persian texts and also can be used in the analysis of the texts and the treatment session of the people who refer to the psychological clinics.